Ecotrons: Powerful and versatile ecosystem analysers for ecology, agronomy and environmental science. (28th January 2021) - Roy, Jacques; Rineau, François; De Boeck, Hans J.; Nijs, Ivan; Pütz, Thomas; Abiven, Samuel; Arnone, John A.; Barton, Craig V. M.; Beenaerts, Natalie; Brüggemann, Nicolas; Dainese, Matteo; Domisch, Timo; et al.
Abstract: Ecosystems integrity and services are threatened by anthropogenic global changes. Mitigating and adapting to these changes require knowledge of ecosystem functioning in the expected novel environments, informed in large part through experimentation and modelling. This paper describes 13 advanced controlled environment facilities for experimental ecosystem studies, herein termed ecotrons, open to the international community. Ecotrons enable simulation of a wide range of natural environmental conditions in replicated and independent experimental units while measuring various ecosystem processes. This capacity to realistically control ecosystem environments is used to emulate a variety of climatic scenarios and soil conditions, in natural sunlight or through broad‐spectrum lighting. The use of large ecosystem samples, intact or reconstructed, minimizes border effects and increases biological and physical complexity. Measurements of concentrations of greenhouse trace gases as well as their net exchange between the ecosystem and the atmosphere are performed in most ecotrons, often quasi continuously. The flow of matter is often tracked with the use of stable isotope tracers of carbon and other elements. Equipment is available for measurements of soil water status as well as root and canopy growth. The experiments ran so far emphasize the diversity of the hosted research. Half of them concern global changes, often with a manipulation of more than one driver. About a quarter deal with the impact of biodiversity loss on ecosystem functioning and one quarter with ecosystem or plant physiology. We discuss how the methodology for environmental simulation and process measurements, especially in soil, can be improved and stress the need to establish stronger links with modelling in future projects. These developments will enable further improvements in mechanistic understanding and predictive capacity of ecotron research which will play, in complementarity with field experimentation and monitoring, a crucial role in exploring the ecosystem consequences of environmental changes. Abstract : Experimentation and modelling are necessary to predict ecosystem functioning under future environments and to develop mitigating and adapting strategies. This paper describes 13 advanced controlled environment facilities, called ecotrons, open to the international community. An ecotron comprises a set of replicated enclosures designed to host ecosystems samples and enable realistic simulations of above‐ and belowground environmental conditions, while simultaneously and automatically measuring ecosystem processes. The characteristics of these infrastructures are given as well as examples of collaborative projects hosted so far.